The unstudied barriers to widespread renewable energy deployment: Fossil fuel price responses - Foster,E; Contestabile,M; Blazquez,J; Manzano,B; Workman,M; Shah,N (Energy Policy, 2017)
Renewable energy policy focuses on supporting the deployment of renewable power generators so as to reduce their costs through scale economies and technological learning. It is expected that, once cost parity with fossil fuel generation is achieved, a transition towards renewable power should continue without the need for further renewable energy subsidies. However, this reasoning implicitly assumes that the cost of fossil fuel power generation does not respond to the large scale penetration of renewable power. In this paper we build a standard economic framework to test the validity of this assumption, particularly in the case of coal and gas fired power generation. We find that it is likely that the cost of fossil fuel power generation will respond to the large scale penetration of renewables, thus making the renewable energy transition slower or more costly than anticipated. More analysis is needed in order to be able to quantify this effect, the occurrence of which should be considered in the renewable energy discourse.